2007
DOI: 10.4049/jimmunol.179.3.1586
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Signals in CD4+ T Cells during Early Contacts with Antigen-Bearing Dendritic Cells in Lymph Node

Abstract: T cell activation by APC requires cytosolic Ca2+ ([Ca2+]i) elevation. Using two-photon microscopy, we visualized Ca2+ signaling and motility of murine CD4+ T cells within lymph node (LN) explants under control, inflammatory, and immunizing conditions. Without Ag under basal noninflammatory conditions, T cells showed infrequent Ca2+ spikes associated with sustained slowing. Inflammation reduced velocities and Ca2+ spiking in the absence of specific Ag. During early Ag encounter, most T cells engaged Ag-presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
82
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 52 publications
7
82
0
Order By: Relevance
“…Most studies have explored calcium responses by introducing T cells loaded with small-molecular fluorochrome indicators in vivo and imaging lymph node explants (32,33). In line with our observation (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Most studies have explored calcium responses by introducing T cells loaded with small-molecular fluorochrome indicators in vivo and imaging lymph node explants (32,33). In line with our observation (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In order to efficiently generate sustained signals necessary for cell activation, lymphocytes must change from an actively motile state to stop crawling when they encounter an APC. This has been shown for T cells where encounter with an APC induce a quick, transient Ca 2+ influx in the T cell, which in turn results in reduced motility [38]. Our data demonstrate that calcium mobilization is a functional property of the NKR-P1F receptor as well as NKR-P1A, although less powerful.…”
supporting
confidence: 63%
“…Later, several studies found that relatively high concentrations of antigen can induce rapid or immediate arrest of transgenic T cells on DCs without an initial phase of T-cell screening. [6][7][8] These data would suggest that T-cell screening of DCs is not obligatory when antigen is abundant. 9 However, the relevance of these findings to immunity with diverse T-cell repertoires is not clear.…”
Section: Introductionmentioning
confidence: 98%